Viral causes of unexplained anterior uveitis in Thailand - Kongyai N. (2014)
Aims To assess the possible role of virus infection in patients with unexplained anterior uveitis (AU). Methods Intraocular fluid and plasma samples of 30 HIV-negative AU patients who were unresponsive or poorly responsive to topical steroid therapy were analyzed for nucleic acid of cytomegalovirus (CMV), herpes simplex virus (HSV), and varicella zoster virus (VZV) by real-time polymerase chain reaction (PCR) and for intraocular antibodies against these viruses by Goldmann-Witmer coefficient (GWC) analysis. Of these 30 cases, 21 were tested forrubella virus by GWC analysis, 16 of which also had PCR assessment of aqueous for rubella virus. Results Viral uveitis determined by either real-time PCR and/or GWC was documented in 20 out of 30 patients (67%). Of 30 paired samples tested by both methods for HSV, CMV, and VZV, 15 showed positive results (CMV (10), HSV (4), and VZV (1)). Real-time PCR was positive in 8/15 (53%), whereas GWC was positive in 10/15 (67%). Out of 10 CMV-positive patients, four had endotheliitis, two had Posner-Schlossman syndrome, and one Fuchs heterochromic uveitis syndrome (FHUS). Five out of 21 (24%) samples tested by GWC for Rubella virus were positive, three of which exhibited clinical features of FHUS. Conclusions Our results indicate that CMV is a major cause of AU in Thailand and show that FHUS can be caused by both CMV and Rubella virus. © 2012 Macmillan Publishers Limited All rights reserved.